Non-suicidal self-injury in Chinese adolescents: longitudinal associations with negative life events and life satisfaction - Xu, Zhansheng; Kong, Yaxin; Yang, Yang; Tian, Mingyangjia; Liu, Yu; Lin, Lin (Frontiers in Psychiatry, 2025)
Objectives The relationship between negative life events, life satisfaction, and nonsuicidal self-injury has been demonstrated in adolescence, but no study has examined the longitudinal associations between the three over time. The present study hypothesized that negative life events play a mediating role in the relationship between life satisfaction and non-suicidal self-injury over time. Methods A total of 268 junior high school students participated in three questionnaires with an interval of half a year and completed questionnaires investigating the Adolescents Self-Harm Scale, the Adolescent Self-Rating Life Events Checklist, and the Satisfaction with Life Scale. Results The results indicated a significant predictive role of negative life events in non-suicidal self-injury over time and the prospective effect of life satisfaction on negative life events in adolescence. Negative life events play an intertemporal mediation in the relationship between life satisfaction and non-suicidal self-injury. Conclusion As a clear non-suicidal self-injury risk factor, negative life events can significantly predict non-suicidal self-injury in adolescence whether it is horizontal or vertical. Junior high school students who are exposed to more negative life events are more likely to have non-suicidal self-injury behaviors and the negative life events have a certain lagging effect on non-suicidal self-injury. Due to the prospective effect of life satisfaction on negative life events in adolescents, negative life events play a mediation in the relationship between life satisfaction and non-suicidal self-injury over time.